2017
DOI: 10.1155/2017/1352948
|View full text |Cite
|
Sign up to set email alerts
|

Review: DNA Barcoding and Chromatography Fingerprints for the Authentication of Botanicals in Herbal Medicinal Products

Abstract: In the last two decades, there has been a tremendous increase in the global use of herbal medicinal products (HMPs) due to their claimed health benefits. This has led to increase in their demand and consequently, also, resulted in massive adulteration. This is due to the fact that most of the traditional methods cannot identify closely related species in a process product form. Therefore the urgent need for simple and rapid identification methods resulted in the discovery of a novel technique. DNA barcoding is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 256 publications
(278 reference statements)
0
25
0
Order By: Relevance
“…Also Abubakar et al [ 42 ] in an effective research have proposed and discussed DNA barcoding in combination with chromatography fingerprints for the authentication of botanical ingredients in herbal medicines.…”
Section: Study Approach About Botanicals and Their Main Plant Compmentioning
confidence: 99%
“…Also Abubakar et al [ 42 ] in an effective research have proposed and discussed DNA barcoding in combination with chromatography fingerprints for the authentication of botanical ingredients in herbal medicines.…”
Section: Study Approach About Botanicals and Their Main Plant Compmentioning
confidence: 99%
“…Thereafter, the f ree extract of inorganic compounds was fractionated and isolated sequentially on preparative, semipreparative and analytical HPLC columns to obtain the target bioactive compound isolates. Reverse Phase HPLC has a broad range of selectivity coupled with a high degree of reproducibility.The retention time of RP-HPLC is longer for less polar molecules; as such, the polar molecules elute more readily (Abubakar, Salleh, Omar, & Wagiran, 2017).…”
Section: Metabolite Profiles Of Ethanolic Extract Of C Racemosamentioning
confidence: 99%
“…It is known that animal-based TMs are mainly derived from animal tissues, organs, or metabolites, and these parts are usually processed into diverse preparations such as slice, powder, and tablet, resulting in difficulties for morphology-based species identification. In addition, several commercial technologies used for species identification, including chromatography and immunoassay, are relatively costly and expertise-dependent, which is not suitable for bulk detection of TM preparations and forensic specimens [ 18 , 19 ]. Therefore, developing an accurate and efficient identification method represents an urgent need for animal-based TM.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decade, advance in molecular techniques has promoted the application of simple and precise DNA analysis in taxonomic field. Among the prevailing genome-based approaches, DNA barcoding provides a robust strategy to identify existing species and discover unknown species via comparative analysis of sequence variation [ 19 21 ]. Extensive studies have shown that DNA barcoding is capable of identifying a wide range of animal species, including mammals, birds, reptiles, amphibians, fishes, and crustaceans [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation